Flora Inventory in the Pantangolemba Village Waterfall Tourism Area, Poso Pesisir Selatan District, Poso Regency - Muhdin, Nining Kasim; Salahuddin, Andi; Angraeni, Endah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pantangolemba Waterfall Tourism Area, located in South Poso Coastal District, Poso Regency, has considerable floral diversity that has not yet been scientifically documented. This study aimed to inventory, identify, and describe the morphological characteristics of flora in the area and to evaluate its potential as a learning resource and a basis for conservation. The study employed a descriptive exploratory approach using the cruise survey method combined with purposive sampling. Species identification was conducted based on morphological characteristics using taxonomic references and online flora databases. The collected data were analyzed descriptively using a qualitative approach. The results revealed a total of nine plant species belonging to seven families, namely Ruellia simplex, Muntingia calabura, Psidium guajava, Syzygium aqueum, Ageratum conyzoides, Peperomia pellucida, Mecardonia procumbens, Musa paradisiaca, and Asystasia gangetica. The vegetation was dominated by herbaceous species, while only three species were classified as trees. Morphological observations demonstrated variations in root systems, stem types, leaf morphology, and reproductive organs, reflecting plant adaptations to the humid environment and varying light intensity of the waterfall ecosystem. The findings indicate that the Pantangolemba Waterfall Tourism Area has strong potential as a natural laboratory, a biology learning resource, and an important baseline for flora management and conservation.